Monitoring Road Works Contracts and Unit Costs for Enhanced Governance in Europe and Central Asia - Alexeeva, Victoria; Queiroz, Cesar; Ishihara, Satoshi (World Bank, Washington, DC, 2014)
The present study generates a specialized dataset of road sector contracts for Bank-financed projects in 14 countries of Europe and Central Asia. The data sample covers 200 completed or ongoing road works contracts signed between 2000 and 2010. Trends for each country are captured through the following indicators: (i) difference between contract values and their engineers' estimates; (ii) cost overruns; (iii) time overruns; (iv) bidding indicators for contracts with and without prequalification: number of firms that applied for prequalification, number of prequalified firms, number of firms that bought bidding documents, number of bidders, number of disqualified bidders; (v) time elapsed between bid opening and contract signing dates; (vi) cost per kilometer of similar works; (vii) road works unit costs; and (viii) ratios between supervision contract values and the related road works contract values. An inventory of risks is developed for each road works contract using a checklist of possible entry points of corrupt activities or red flags. The frequency of observations is measured for the selected types of red flags from a sample of 200 road works contracts surveyed. The contracts with complaints received by the Bank's Integrity Vice Presidency (INT) are examined separately to check if they exhibit a pattern of indicators consistent with the presence of allegations of corruption or fraud. The study looks further into the determinants of road rehabilitation and reconstruction costs. It concludes with selected recommendations to sustain the platform fostering governance and integrity in the procurement and implementation of road sector contracts under Bank-funded operations.